Intramuscular stiffness distribution in anterior and posterior upper trapezius muscles in healthy young males - Sasaki, Kohei; Miyamoto, Naokazu (Frontiers in Sports and Active Living, 2024)
Introduction Increased muscle stiffness in the upper trapezius has been suggested to be associated with cervical myofascial pain and myofascial trigger points (MTrP). Recently, efforts have been made to objectively detect MTrP using ultrasound shear wave elastography (SWE). However, there is no consensus on the relationship between muscle stiffness assessed by SWE and MTrP. This may be due to the possibility that muscle stiffness is not uniform even in the asymptomatic trapezius. The present study aimed to characterize passive muscle stiffness at the proximal, central, and distal sites of the anterior and posterior parts of the upper trapezius. Methods Seventeen healthy young males without neck pain participated in the study. The upper trapezius was divided into anterior and posterior parts based on anatomical landmarks: the line between C6 and the lateral end of the clavicle was defined as the anterior part, while the line between C7 and the acromion angle was defined as the posterior part. Shear wave speed (SWS; an index of stiffness) was measured using ultrasound SWE at six sites in the anterior and posterior parts of the upper trapezius, at 25% (proximal), 50% (central), and 75% (distal) of the muscle belly length. Results SWS in the anterior part was significantly higher at the proximal (p < 0.001) and distal (p < 0.001) sites than at the central site. In the posterior part, there was no significant difference in SWS between the proximal, central, and distal sites. Comparisons between the anterior and posterior parts showed no significant differences in SWS at the proximal (p = 0.147), central (p = 0.339), and distal sites (p = 0.051). Conclusions The characteristics of passive stiffness distribution in the anterior and posterior parts of the upper trapezius have important implications with respect to the optimal location of the control point during MTrP detection. In particular, it may be preferable to set the control point for detecting MTrP in the transverse direction rather than in the fascicle direction, that is, to compare passive muscle stiffness at the same levels between the anterior and posterior parts.